Investment casting using fused deposition modelling - Lee, Chee Wai. (2008)
A benchmark model is designed to investigate the feasibility of employing a commercially available RP process, Fused Deposition Modelling (FDM), to fabricate acrylonitrile butadiene styrene (ABS) and wax (ICW06) parts as direct sacrificial patterns for IC.